(n, n(n − 1), n − 1) Permutation codes based on packing and Mendelsohn designs. Issue 23 (1st November 2016) - Peng, Li
Abstract : Mendelsohn design was first used to construct n − 1 blocks of one optimal 2−( n, n, 2) packing which is isomorphic to an ( n, n − 1, n − 1) permutation array. The n ‐ary shift register (SR) formed by a group of k binary SRs of length n was constructed and then used to operate n − 1 blocks of the 2−( n, n, 2) packing which can generate n ( n − 1) blocks of another optimal 2−( n, n, 2 n ) packing from which a family of ( n, n ( n − 1), n − 1) permutation codes can be constructed.